Luzindole and 4P-PDOT block the effect of melatonin on bovine granulosa cell apoptosis and cell cycle depending on its concentration - Wang, Shujuan; Liu, Wenju; Wen, Aiyou; Yang, Bing; Pang, Xunsheng (PeerJ, 2021)
Granulosa cells play an essential physiological role in mediating the follicle development and survival or apoptosis of granulosa cells dictate the follicle development or atresia. The aim of this study was to investigate the role of high dose (10−5 M) and low dose (10−9 M) melatonin in bovine granulosa cells, and assess whether MT1 and MT2 inhibiter affect granulosa cells response to melatonin. We found that the high dose (10−5 M) and low dose (10−9 M) both could act as an essential role in modulating granulosa cells apoptosis, cell cycle and antioxidant. The beneficial effect could be related to that melatonin promoted the expression of Bcl2, Bcl-xl, SOD1 and GPX4, and inhibited Bax, caspase-3 and p53 expression. Moreover P21 expression was decreased in granulosa cells treated with the high dose (10−5 M) melatonin and increased in that treated with the low dose (10−9 M) melatonin. To further reveal the role of MT1 and MT2 in mediating the effect of melatonin on granulosa cells apoptosis, cell cycle and antioxidant, we found that the luzindole and 4P-PDOT did not affect the effect of high dose (10−5 M) melatonin on regulating Bcl2, Bax, caspase-3, SOD1, GPX4 and p53 expression, while blocked its effect on modulating Bcl-xl and P21expression. However, luzindole and 4P-PDOT disturbed the effect of low dose (10−9 M) melatonin on regulating Bcl2, Bax, caspase-3, Bcl-xl, SOD1, GPX4, and p53 expression. In conclusion, these results reveal that the effect of low dose (10−9 M) melatonin on granulosa cells apoptosis are mediated by MT1 and MT2, and the high dose (10−5 M) melatonin affect the granulosa cells apoptosis by other pathway, besides MT1 and MT2. Moreover MT1 and MT2 may work in concert to modulate bovine granulosa cells function by regulating cellular progression and apoptosis.
Keywords: Melatonin; Melatonin receptor antagonist; Bovine; Granulosa cell; Gene regulation